The Role of TASK-2 Channels in CO2 Sensing in Zebrafish (Danio rerio) - Koudrina, Natalia (Université d'Ottawa / University of Ottawa, 2017)
Fish naturally experience fluctuating levels of O2 and CO2 in their environment. To cope with the deleterious effects of lowered O2 (hypoxia) or elevated CO2 (hypercapnia), fish exhibit an array of cardiorespiratory adjustments aimed at preserving homeostasis. One of the most significant of these responses is reflex hyperventilation. In zebrafish (Danio rerio), hyperventilation during hypoxia or hypercapnia is thought to be initiated by the activation of chemoreceptor cells, termed neuroepithelial cells (NECs) which detect changes in ambient levels of O2 or CO2. The NECs of larval zebrafish are found throughout the integument and recent studies have shown that these NECs likely mediate the ventilatory responses to hypoxia and the cardiac responses to hypercapnia. However, no study has yet examined the ventilatory response of larval zebrafish to hypercapnia and regardless of developmental stage, the signalling pathways involved in CO2 sensing remain unclear. In the mouse, a background potassium channel (TASK-2) was shown to contribute to the sensitivity of chemoreceptor cells to CO2. Zebrafish have two specific TASK-2 channel paralogs encoded by kcnk5a and kcnk5b. The purpose of this thesis was to determine whether TASK-2 channels are expressed in NECs of larval zebrafish and whether they are involved in CO2 sensing. Immunohistochemical approaches were used to visualize TASK-2 protein (encoded by kcnk5a) within NECs of larvae and adult gill. TASK-2 protein was observed on NECs in both larvae and adult gill. Exposure of larvae to hypercapnia caused an increase in cardiac and breathing frequencies; these responses were blunted in fish experiencing either TASK-2 and/or TASK-2b knockdown. The results of these experiments suggest that TASK-2 has a role in activating NECs thus eliciting cardiorespiratory responses, when larvae are exposed to hypercapnia.
Keywords: CO2 sensing; TASK-2